Padronização dos critérios de seleção em estudos sobre medicações nasais - Borin, Andrei; Abib Jr., Eduardo; Araujo, Cleomines Izidio; Martinez, Luis Lopez [UNESP]; Rodrigues, Heloisio (FapUNIFESP (SciELO), 2009)
Clinical studies on nasal topical medications require the standardization of nasosinusal normality in order to establish control groups through a specific evaluation of the upper airways. Aim: to standardize the evaluation of candidates for control groups in clinical studies on nasal topical medications. Material and Methods: healthy male volunteers of 18 to 50 years of age, asymptomatic from the nasosinusal standpoint were subjected to a sequential and excluding assessment made up of clinical evaluation, immediate hypersensitivity skin test, saccharin test, flexible nasofibroscopy and nasal cytology. Study design: Crosssectional contemporary cohort. Results: Of the 33 people originally enrolled, 14 (42.4%) were excluded for clinical reasons. Of the 19 remaining, 2 (10.5%) had atopy diagnosed in the skin test and were excluded. 17 were tested with saccharin and presented normal mucociliary clearance. Evaluation by nasal endoscopy showed abnormality in 2 cases (11.8%) and these were excluded. The remaining 15 were submitted to nasal cytology, which proved normal, representing 45.5% of those initially included. Conclusion: The proposed protocol for sequential and excluding evaluation was effective in defining candidates for the establishment of control groups in clinical studies on nasal topical medications. © Revista Brasileira de Otorrinolaringologia. All Rights reserved.
Standardizing selection criteria in nasal medication studies
Keywords: Control groups; Cytology; Mucociliary clearance; Nose; Skin tests; diagnostic agent; saccharin; adolescent; adult; case control study; cross-sectional study; human; immediate type hypersensitivity; intranasal drug administration; male; middle aged; mucociliary clearance; patient selection; skin test; Administration, Intranasal; Adolescent; Adult; Case-Control Studies; Cross-Sectional Studies; Humans; Hypersensitivity, Immediate; Male; Middle Aged; Mucociliary Clearance; Patient Selection; Saccharin; Skin Tests; Young Adult